Relationship of fibroblast growth factor 21, Klotho, and diabetic retinopathy: a meta-analysis - Jiang, Yanhua; Zhang, Weilai; Xu, Yao; Zeng, Xiandong; Sun, Xin (Frontiers in Endocrinology, 2024)
Background: Diabetic retinopathy (DR) is a serious microvascular complication of diabetes mellitus. Research has identified a close relationship between fibroblast growth factor 21 (FGF21) and DR. FGF21 is a member of the FGF subfamily, which is activated by the Klotho coenzyme involved in the occurrence of DR. However, the association between FGF21, Klotho, and DR remains controversial.Aim: To assess FGF21 and Klotho levels in patients with DR.Methods: A literature search of the Web of Science, Wiley Online Library, PubMed, China National Knowledge Infrastructure and Wanfang databases was performed. The title or abstract search terms "diabetic retinopathy" and "DR" were used in combination with "fibroblast growth factor 21", "FGF21", and "Klotho". Meta-analysis results are presented as standardized mean difference (SMD) with corresponding 95% confidence interval (CI).Results: Fifteen studies were included in this meta-analysis. FGF21 levels in patients with DR were significantly higher than in non-DR patients with diabetes (SMD: 2.12, 95% CI [1.40, 2.84]). Klotho levels in patients with DR were significantly lower than in non-DR patients with diabetes (SMD: -0.63, 95% CI [-1.22, -0.04]).This systematic review is the first to evaluate the relationship between FGF21, Klotho levels, and DR. FGF21 levels were significantly higher in patients with DR. Fully elucidating the role of FGF21 will significantly contribute to the treatment of DR.